Looking at gender is not enough—How diversity of farmers’ marginalization relates to varietal trait preferences - Bacud, Eva Salve Tino; Gerullis, Maria Katharina; Puskur, Ranjitha; Heckelei, Thomas (Elsevier, 2024)
Improved crop varieties help farmers adapt to changing climate and socioeconomic challenges. They are essential for meeting the global food demand, but their adoption remains slow and low. One reason for this unsuccessful adoption is the disregard of trait preferences and marginalized contexts of diverse users by actors in varietal development and delivery. The general wisdom regarding trait preferences includes gender-distinct priorities, in which men focus on high yield and marketability, while women prefer good taste and other cooking attributes. However, although gender is a first step toward nuanced preferences, most analyses restrict themselves to gender-based comparisons (frequently using the sex of heads of households), which homogenizes socioeconomic conditions and preferences within gender. Using intrahousehold preference data, our study reveals that the intersection between gender and other social categories presents compounded marginalization that corresponds to similarities or differences in women’s and men’s trait preferences. Cluster analysis reveals that trait preferences of women and men overlap but differ in the traits’ relative importance. Trait preferences are comparable in low-wealth clusters as they operate in similar marginalized contexts and diverge in high-wealth clusters. Furthermore, logit regression shows that factors of marginalization, gender roles, and agency are associated with increased odds of prioritizing specific traits, such as market and culinary traits. Our results demonstrate how diversity of marginalization and intersectionality matters more than gender dichotomies. We anticipate that our intersectional approach to understanding gendered trait preferences can enhance targeted, demand-led, and inclusive varietal development and delivery in the future.